Antibiotic Resistance and Genetic Profiles of Vibrio parahaemolyticus Isolated from Farmed Pacific White Shrimp (Litopenaeus vannamei) in Ningde Regions - Fangfang Zhang; Jie Zhang; Guowen Lin; Xiaoqiang Chen; Huizhen Huang; Chunxia Xu; Hai Chi (Microorganisms, 2024)
To better understand the antibiotic resistance, virulence genes, and some related drug-resistance genes of Vibrio parahaemolyticus in farmed pacific white shrimp (Litopenaeus vannamei) in Ningde regions, Fujian province, we collected and isolated a total of 102 strains of V. parahaemolyticus from farmed pacific white shrimp in three different areas of Ningde in 2022. The Kirby–Bauer disk method was used to detect V. parahaemolyticus resistance to 22 antibiotics, and resistant genes (such as quinolones (qnrVC136, qnrVC457, qnrA), tetracyclines (tet A, tetM, tetB), sulfonamides (sulI, sulII, sulIII), aminoglycosides (strA, strB), phenicols (cat, optrA, floR, cfr), β-lactams (carB), and macrolides (erm)) were detected by using PCR. The findings in this study revealed that V. parahaemolyticus was most resistant to sulfamoxazole, rifampicin, and erythromycin, with resistance rates of 56.9%, 36.3%, and 33.3%, respectively. Flufenicol, chloramphenicol, and ofloxacin susceptibility rates were 97.1%, 94.1%, and 92.2%, respectively. In all, 46% of the bacteria tested positive for multi-drug resistance. The virulence gene test revealed that all bacteria lacked the tdh and trh genes. Furthermore, 91.84% and 52.04% of the isolates were largely mediated by cat and sulII, respectively, with less than 5% resistance to aminoglycosides and macrolides. There was a clear mismatch between the antimicrobial resistance phenotypes and genotypes, indicating the complexities of V. parahaemolyticus resistance.